Case Report: Optimized guidewire pacing in transcatheter aortic valve replacement combined with complex PCI in a patient with severe aortic stenosis and regurgitation - Ma, Ruisong; Liao, Wang; Zhang, Lili; Wang, Sheng (Frontiers in Cardiovascular Medicine, 2025)
Left ventricular (LV) guidewire pacing has been proven to be a safe and effective pacing mode for transcatheter aortic valve replacement (TAVR). However, the high pacing voltage threshold and impedance of LV guidewire pacing are potential risks for loss of capture and valve embolization. Moreover, decisions surrounding whether and when to perform percutaneous coronary intervention (PCI) are always heterogeneous in patients with severe aortic stenosis and coronary artery disease. As described in this case report, we attempted an optimized LV guidewire pacing mode with the lowest pacing voltage threshold and impedance, avoiding complications associated with additional vascular access and further reducing TAVR costs. In addition, we successfully performed simultaneous PCI in this patient with a vertically downward orifice of the right coronary artery (RCA), severe calcified stenosis in the RCA, horizocardia, and a dilated ascending aorta. This case report provides new evidence for LV guidewire pacing and the opportunity for PCI in TAVR procedures.